X-efficiency and its impact on bank’s stock performance-Evidence from Mainland China and Hong Kong - GAO, Yue (2019)
This paper examines the X-efficiency of banks in mainland China and Hong Kong and its impact on banks’ stock performance from 2011 to 2018. We apply SFA (Stochastic Frontier Analysis) and translog cost function to obtain X-efficiency scores and find mainland banks are more cost efficient than Hong Kong banks. The average X-efficiency scores for these two regions are 92.03% and 65.95% respectively. The system Generalized Method of Moments (GMM) is employed in our study to investigate the relationship between X-efficiency and bank’s cumulative annual stock returns (CASR). X-efficiency is found to have a significant and positive relationship with CASR. We also investigate the determinants of CASR by including other variables into the model. Besides X-efficiency, other four variables are found to have a significant impact on CASR.